An PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SCRATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V DI SDN SIMAJA : Media - Fatimah, Siti; Hema Widiawati; Novan Hardiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to determine the effect of using Scratch as a learning medium on the mathematics learning outcomes of fifth-grade students at SDN Simaja. The background of this research is the low student achievement, which is attributed to the use of unengaging and non-interactive instructional media. The study employed a quantitative method with a One-Group Pretest-Posttest Design. The sample consisted of 22 students. The instruments used were pretest and posttest assessments to measure cognitive learning outcomes, and observation sheets to assess affective and psychomotor aspects. The results revealed a significant improvement in mathematics learning outcomes after the implementation of Scratch media. The students' average score increased from 59.09 (pretest) to 82.37 (posttest), while the percentage of students achieving the minimum mastery criteria rose from 22.73% to 81.82%. The paired sample t-test showed a significance value of 0.000 and a t-value of 15.603 > t-table value of 2.079, indicating a statistically significant difference in learning outcomes before and after using Scratch. The N-Gain score obtained was 0.6616, categorized as moderate, suggesting that the use of Scratch is reasonably effective. Therefore, it can be concluded that the use of Scratch as a learning medium is effective in improving the mathematics learning outcomes of fifth-grade students at SDN Simaja.